ANALISIS KESALAHAN DALAM MATERI STATISTIKA PADA SISWA SMP KELAS IX BERDASARKAN DARI PERSPEKTIF GENDER - Oke Puji Rahayu; Ratni Purwasih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study aims to analyze student errors in statistical material reviewed based on a gender perspective. The method used is descriptive qualitative with statistical material. Researchers want to explore in depth how the mistakes or negligence of students in the process of solving the statistical material with the given written test. The population in this study were all students of class IX at one of the MTs in the city of Cimahi by taking a sample of 10 people, namely male and female students. The instrument used was a written test with 5 questions in the description. The data analysis technique in this research is to calculate the score of the answers, add up the results of each question and then calculate the average, then interpret the results of the difficulty based on data criteria. The results showed that both male and female students were able to complete the written test quite well. It's just that it has a slight difference in the understanding process and the completion process.